Self-Perceived Fitness in Young Athletes: Associations with Anthropometric Markers and Lipid Profile as Cardiometabolic Risk Factors—COR-SCHOOL Study - Alvaro Pano-Rodriguez; Saül Aixa-Requena; Abraham Batalla-Gavaldà; Jose Vicente Beltran-Garrido; Isaac López-Laval; Vicenç Hernández-González; Carme Jové-Deltell; Enric Conesa-Milian; Joaquin Reverter-Masia (Journal of Functional Morphology and Kinesiology)
Objective: This study analyzed the relationship between self-perceived physical fitness and anthropometric and biochemical variables in young athletes from extracurricular sports programs in northeastern Spain. Methods: A cross-sectional design was used with a sample of 673 young athletes. Data collection included self-reported physical fitness and objective anthropometric and biochemical measurements. The analysis explored associations between perceived fitness dimensions and physical/biochemical variables, with attention to sex differences. Results: Fat mass showed significant inverse associations with all perceived fitness dimensions: general fitness (OR = 0.62, 95% CI [0.41, 0.94]), cardiorespiratory fitness (OR = 0.56, 95% CI [0.37, 0.83]), muscular strength (OR = 0.61, 95% CI [0.41, 0.91]), speed/agility (OR = 0.59, 95% CI [0.39, 0.88]), and flexibility (OR = 0.57, 95% CI [0.39, 0.84]). Higher fat mass was consistently linked to lower perceived fitness. HDL levels were positively associated with general (OR = 1.40, 95% CI [1.13, 1.74]) and cardiorespiratory fitness (OR = 1.32, 95% CI [1.07, 1.62]), while LDL levels showed no significant effect (p > 0.05). Sex differences emerged for general fitness (OR = 0.52, 95% CI [0.33, 0.82]) and flexibility (OR = 0.51, 95% CI [0.33, 0.78]), favoring boys, but no differences were found for cardiorespiratory fitness, muscular strength, or speed/agility (p > 0.05). This suggests that shared athletic environments may reduce typical sex-based disparities. Conclusions: Our findings emphasize the importance of considering both anthropometric and biochemical variables when evaluating perceived fitness in youth athletes. Regular athletic engagement may buffer sex-based differences in fitness perception.